Experiences of Midwives in Turkey Regarding Providing Childbirth Care to Women With COVID-19: A Qualitative Study - Ayla Ergin; Meltem Demirgöz Bal; Özlem Aşcı (Atatürk University, 2024)
Objective: The aim of the study was to assess the experiences of midwives in providing childbirth care to women with coronavirus disease 2019 (COVID-19). Methods: This qualitative study was conducted with 25 midwives who worked in a public hospital for at least one year and actively provided childbirth care to women with COVID-19 between 15-30 January 2021.The data were obtained through one-to-one video conference interviews using a semi-structured interview form consisting of seven open-ended questions prepared by the researchers and analyzed thematically. Results: Four main themes were identified. Theme 1: 'Change in midwifery care performance' describes the performance of midwives in providing childbirth care to women with COVID-19 and the influencing factors. Theme 2: 'Unusual labour and delivery' explained the isolation processes of midwives in labour and birth, the changes they experience regarding the acceptance of a birth partner during the birth, and the way they handle the increasing number of cesarean section decisions. Theme 3: 'Strict policies that disrupt postpartum care', explained the practices of midwives in the postpartum period, which changed with political decisions. Theme 4: 'Emotional problems' explain the emotional problems directly experienced from a professional and human perspective. Conclusion: In the COVID-19 period, midwives preserved their compassion and empathy, but had difficulty providing woman-centered care. They defended natural birth, but could not have their say in the changes. Anxiety, fear, increased stress, and burnout significantly affected the professional quality of life.